subtract the sum of minus three by two and two by three from the sym of four by three and minus fuve by six
Answers
Answered by
1
answer
![(\frac{ - 3}{2} + \frac{3}{2} ) - ( \frac{4}{3} + \frac{ - 5}{6}) (\frac{ - 3}{2} + \frac{3}{2} ) - ( \frac{4}{3} + \frac{ - 5}{6})](https://tex.z-dn.net/?f=+%28%5Cfrac%7B+-+3%7D%7B2%7D+%2B+%5Cfrac%7B3%7D%7B2%7D+%29+-+%28+%5Cfrac%7B4%7D%7B3%7D+%2B+%5Cfrac%7B+-+5%7D%7B6%7D%29)
LETS SOLVE
![( \frac{4}{3} + \frac{ - 5}{6} ) ( \frac{4}{3} + \frac{ - 5}{6} )](https://tex.z-dn.net/?f=%28+%5Cfrac%7B4%7D%7B3%7D+%2B+%5Cfrac%7B+-+5%7D%7B6%7D+%29)
LCM OF 3 AND 6 = 6
![( \frac{8}{6} + \frac{ - 5}{6} ) = \frac{ - 3}{6} = \frac{ - 1}{2} ( \frac{8}{6} + \frac{ - 5}{6} ) = \frac{ - 3}{6} = \frac{ - 1}{2}](https://tex.z-dn.net/?f=%28+%5Cfrac%7B8%7D%7B6%7D+%2B+%5Cfrac%7B+-+5%7D%7B6%7D+%29+%3D+%5Cfrac%7B+-+3%7D%7B6%7D+%3D+%5Cfrac%7B+-+1%7D%7B2%7D+)
LETS SOLVE
![( \frac{ - 3}{2} + \frac{2}{3} ) ( \frac{ - 3}{2} + \frac{2}{3} )](https://tex.z-dn.net/?f=%28+%5Cfrac%7B+-+3%7D%7B2%7D+%2B+%5Cfrac%7B2%7D%7B3%7D+%29)
LCM OF 2 AND 3 = 6
![( \frac{ - 9}{6} + \frac{4}{6} ) = \frac{ - 5}{6} ( \frac{ - 9}{6} + \frac{4}{6} ) = \frac{ - 5}{6}](https://tex.z-dn.net/?f=%28+%5Cfrac%7B+-+9%7D%7B6%7D+%2B+%5Cfrac%7B4%7D%7B6%7D+%29+%3D+%5Cfrac%7B+-+5%7D%7B6%7D+)
NEXT STEP
![( \frac{ - 5}{6} - \frac{ - 3}{6} ) = \frac{ - 8}{6} = \frac{ - 4}{3} ( \frac{ - 5}{6} - \frac{ - 3}{6} ) = \frac{ - 8}{6} = \frac{ - 4}{3}](https://tex.z-dn.net/?f=+%28+%5Cfrac%7B+-+5%7D%7B6%7D+-+%5Cfrac%7B+-+3%7D%7B6%7D+%29+%3D+%5Cfrac%7B+-+8%7D%7B6%7D+%3D+%5Cfrac%7B+-+4%7D%7B3%7D+)
ANSWER
LETS SOLVE
LCM OF 3 AND 6 = 6
LETS SOLVE
LCM OF 2 AND 3 = 6
NEXT STEP
ANSWER
saibal29:
thanks a ton
Similar questions